Utility of echocardiographic right ventricular subcostal strain in critical care. (23rd June 2021) - Bleakley, Caroline; de Marvao, Antonio; Morosin, Marco; Androulakis, Emmanouil; Russell, Clare; Athayde, Andre; Cannata, Antonio; Passariello, Maurizio; Ledot, Stéphane; Singh, Suveer; Pepper, John; Hill, Jonathan; et al.
Abstract: Aims: Right ventricular (RV) strain is a known predictor of outcomes in various heart and lung pathologies but has been considered too technically challenging for routine use in critical care. We examined whether RV strain acquired from the subcostal view, frequently more accessible in the critically ill, is an alternative to conventionally derived RV strain in intensive care. Methods and results: RV strain data were acquired from apical and subcostal views on transthoracic echocardiography (TTE) in 94 patients (35% female), mean age 50.5 ± 15.2 years, venovenous extracorporeal membrane oxygenation (VVECMO) (44%). RV strain values from the apical (mean ± standard deviation; –20.4 ± 6.7) and subcostal views (–21.1 ± 7) were highly correlated (Pearson's r –0.89, P < 0.001). RV subcostal strain correlated moderately well with other echocardiography parameters including tricuspid annular plane systolic excursion ( r –0.44, P < 0.001), RV systolic velocity (rho = –0.51, P < 0.001), fractional area change ( r –0.66, P < 0.01), and RV outflow tract velocity time integral ( r –0.49, P < 0.001). VVECMO was associated with higher RV subcostal strain (non-VVECMO –19.6 ± 6.7 vs. VVECMO –23.2 ± 7, P = 0.01) but not apical RV strain. On univariate analysis, RV subcostal strain was weakly associated with survival at 30 days ( R 2 = 0.04, P = 0.05, odds ratio =1.08) while apical RV was not ( P = 0.16). Conclusion : RV subcostal deformation imaging is a reliable surrogate for conventionally derived strain in critical care and may in time prove to be a useful diagnostic marker in this cohort.